(untitled) (Manila, 2003)
Contents: Abbreviations; Integrated strategies to reduce vehicle emissions; New vehicule standards; Inspection and mantenance (I/M); Special considerations for fuels and lubricants...
Keywords: Air,Không khí; Pollution,Ô nhiễm; Asia,Châu Á